2012
DOI: 10.1371/journal.pone.0030685
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Protein Malnutrition Does Not Impair Insulin Secretion from Pancreatic Islets of Offspring after Transplantation into Diabetic Rats

Abstract: Pancreatic islets from adult rats whose mothers were protein restricted during lactation undersecrete insulin. The current work analyzes whether this secretory dysfunction can be improved when the pancreatic islets are grafted into hyperglycemic diabetic rats. Two groups of rats were used: the adult offspring from dams that received a low protein diet (4%) during the initial 2/3 of lactation (LP) and, as a control, the adult offspring from dams that consumed a normal protein diet (23%) during the entire period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…38 Recently, elegant studies reported that transplantation of pancreatic islets, from offspring whose mothers were protein restricted during lactation, was able to regulate fasting blood glucose concentrations in diabetic rats. 39 These results reinforce the idea that pancreatic islets from perinatally undernourished animals are not altered per se but presumably show a reduced number that may explain why β-cells are less sensitive to glucose stimulation. This decreased β-cell mass would explain the intolerance to glucose frequently observed in offspring from malnourished mothers.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…38 Recently, elegant studies reported that transplantation of pancreatic islets, from offspring whose mothers were protein restricted during lactation, was able to regulate fasting blood glucose concentrations in diabetic rats. 39 These results reinforce the idea that pancreatic islets from perinatally undernourished animals are not altered per se but presumably show a reduced number that may explain why β-cells are less sensitive to glucose stimulation. This decreased β-cell mass would explain the intolerance to glucose frequently observed in offspring from malnourished mothers.…”
Section: Discussionsupporting
confidence: 82%
“…It seems plausible that insulin production might not be sufficient to regulate glycemia in response to glucose challenge, as it has been reported that adult male rats from perinatally undernourished mothers present decreased β-cell mass associated with insulinopenia and marked glucose intolerance 38 . Recently, elegant studies reported that transplantation of pancreatic islets, from offspring whose mothers were protein restricted during lactation, was able to regulate fasting blood glucose concentrations in diabetic rats 39 . These results reinforce the idea that pancreatic islets from perinatally undernourished animals are not altered per se but presumably show a reduced number that may explain why β-cells are less sensitive to glucose stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results showed no change in either β-cell metabolism or calcium buffering, an impairment of cholinergic transduction was reported [ 73 ]. Surprisingly, diabetic rats transplanted with pancreatic islets from adult rats that were protein-restricted during lactation showed improvement of their fasting glycemic, which may indicate that changes in β-cell activity provoked by poor perinatal protein nutrition are not permanent and could open possibilities to new therapeutics to treat metabolic diseases [ 74 ].…”
Section: Introductionmentioning
confidence: 99%